Numerical simulation of timber connectors based on a fracture strength characterization of radiata pine wood - Saavedra-Flores, E; Yanez-Cart, S (Elsevier Ltd, 2025)
Wood has gained significant importance in construction in recent years, yet some species, such as Chilean radiata pine, lack comprehensive research on their mechanical behavior and material parameters. Timber exhibits variable and often quasi-brittle mechanical properties, making the identification of fracture strength parameters crucial for accurate structural predictions. This paper presents a methodology for characterizing fracture strength in Chilean radiata pine using finite element simulations with phenomenological models originally developed for composite materials. The methodology employs Design of Experiments and optimization algorithms to fit strength parameters, which are then validated against experimental results from tensile, three-point, and four-point bending tests. Additionally, the study focuses on the simulation of timber connectors (simple and toothed plate) in double shear resistance tests. Experimental tests were conducted, and a computational model was developed to replicate these tests. The results show that the simulated behavior of both the material and the connections closely matches experimental findings in terms of load-bearing capacity. The proposed approach for strength parameter identification proves suitable for the structural characterization of timber connectors, even with limited or scattered experimental data. It enables robust and accurate determination of material parameters and connector performance, reducing the need for extensive experimental testing and ensuring reliable structural characterization. Moreover, the methodology highlights the importance of brittle fracture in the mechanical performance of structural timber connectors. © 2025 Institution of Structural Engineers. Published by Elsevier Ltd. All rights are reserved, including those for text and data mining, AI training, and similar technologies.